Image resources and textual elements from the perspective of Information Design in the Coronavirus SUS application - Jorente, Maria José Vicentini [UNESP]; Silva, Stephanie Cerqueira (My University, 2022)
The access and sharing of information have been constantly modified, due to the transformations of Information and Communication Technologies, which have provided a horizontal communication of different actors on the Web platform. In the recent case of the coronavirus pandemic, several countries carried out rapid and frequent communication around the world and, in some cases, developed their own digital informational environments. In Brazil, the Coronavirus SUS app was created in order to raise awareness of the Covid-19 disease. Thus, in order to understand how the interdisciplinarity between Information Design and Information Science proposes resources for the organization and presentation of information, in relation to image resources and textual elements, the objective of this article is to verify the contributions of such interdisciplinarity in the planning of information for sharing them in digital environments on the Web, focusing on the Coronavirus SUS application, based on the principles of Design and Information Design, according to Rowland (1993), Lipton (2007) and Pettersson (2010). The article is qualitative in nature and is based on the level of descriptive-exploratory research; the application's interfaces and functionalities were described and verified, according to the elements of verification of the Design and Information Design principles. The results showed the focus on a visual proposal, in which many aesthetic-formal principles of Design and Information Design were not contemplated, which interfered in the functionality and usefulness for the infocommunication process with informational subjects and communities of interest. It is considered that the interdisciplinarity between Information Design and Information Science establishes potentiating concepts for the organization and presentation of information, focusing on progressive improvements in the quality of access and sharing of information, translated into the post-custodial paradigm.
Recursos imagéticos e elementos textuais sob a perspectiva do Design da Informação no aplicativo Coronavírus SUS
Recursos imagéticos e elementos textuais sob a perspectiva do Design da Informação no aplicativo Coronavírus SUS
Keywords: Digital Environments; Information Design; Information Science